Pengetahuan dan Implementasi Konsep Amal Maruf dan Amal Munkar Pada Siswa di SMA Negeri 1 Tempel - Novita Sari (FAI UMY, 2017)
Pengetahuan dan Implementasi Konsep Amal Maruf dan Amal Munkar Pada Siswa di SMA Negeri 1 Tempel